2013
DOI: 10.4322/rca.2013.094
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative propagation of redberry using refrigeration, IBA and BAP

Abstract: Increasing interest in the cultivation of redberries has created a need to optimize seedling propagation. This work examines techniques for the vegetative propagation of redberry. Four sequential experiments were conducted. In the first two experiments, we collected stem and root cuttings. In the first experiment, the cuttings were treated with different IBA concentrations, 0, 1000, 2000, 3000 and 4000 mg L-1 , for 10 s. In the second experiment, the cuttings were separated into bundles of ten cuttings each an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(11 reference statements)
0
2
0
3
Order By: Relevance
“…Uma delas é o armazenamento em ambiente refrigerado e úmido, cuja finalidade é suprir a necessidade de frio das gemas, em fruteiras de clima temperado (PATTO et al, 2013). Este armazenamento auxilia na superação da endodormência das gemas e propicia o aumento da emissão de brotações nas estacas (CELANT et al, 2010).…”
Section: Indroduçãounclassified
See 1 more Smart Citation
“…Uma delas é o armazenamento em ambiente refrigerado e úmido, cuja finalidade é suprir a necessidade de frio das gemas, em fruteiras de clima temperado (PATTO et al, 2013). Este armazenamento auxilia na superação da endodormência das gemas e propicia o aumento da emissão de brotações nas estacas (CELANT et al, 2010).…”
Section: Indroduçãounclassified
“…O ácido indolilbutírico (AIB) é uma auxina sintética que tem por finalidade aumentar a emissão de raízes em estacas caulinares (CHAGAS et al, 2008;HAN et al, 2009;PATTO et al, 2013).…”
Section: Indroduçãounclassified
“…Los resultados encontrados, muy posiblemente se debe a que la suplementación exógena de IBA causó un efecto f itotóxico en la planta, reduciendo el enraizamiento y por consecuencia la muerte de la plántula. Resultados reportados por Patto et al (2013) mostraron tendencias similares a las del presente estudio; indicando que la emisión de raíces y brotes disminuyó ligeramente con la aplicación de concentraciones de IBA, obteniendo mayor emisión de raíces y brotes en el testigo. Así mismo Štefančic, Štampar y Osterc ( 2005) hacen mención que IBA inhibió la formación de brotes nuevos en el período temprano del desarrollo de la raíz, influyendo negativamente en el crecimiento de los brotes y el desarrollo del tipo acrobasal del sistema de enraizamiento.…”
Section: Sobrevivencia De Plantas Trasplantadas Con Tratamientos De áCido Indol-3-butírico (Iba)unclassified
“…A rooting study of root and semi-woody stem cuttings of red raspberry indicated that IBA was not necessary for the rooting of root cuttings (PATTO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%